Effect of Solid Loading on Carbon Dioxide Absorption in Bubble Column - Khadhier Mageed, Alyaa (Al-Khwarizmi Engineering Journal, 2011)
In the present work experiments were conducted to study  the effect of solid loading (1,5 and 9 vol.%) on the enhancement of carbon dioxide absorption in bubble column at various volumetric gas flow rate (0.75, 1 and 1.5 m3/h) and absorbent concentration (caustic soda)( 0.1,0.5 and 1 M  ). Activated carbon and alumina oxide (Al2O3) are used as solid particles. The Danckwerts method was used to calculate interfacial area and individual mass transfer coefficients during absorption of carbon dioxide in a bubble column. The results show that the absorption rate was increased with increasing volumetric gas flow rate, caustic soda concentration and solid loading. Mass transfer coefficient and interfacial area were increased with increasing volumetric gas flow rate, and solid loading.